(3GdLZQGajI hGdeJZjQGJ GdOhdjI GdLjhSjGSjI (B-(3GdLjhGbJUGOjIs - (3eLjO edhc(B, (3GdSGeQGFjs ((3YeGf(B:s (3OGQ GdjGRhQj GdYdejI ddfTQ hGdJhRjY(B,s, 2023)
(3jbOe gPG GdcJGH OQGSI TGedI ddYdGbI Hjf GdLZQGajG hGdeJZjQGJ GdOhdjI GdLjhSjGSjI hGdLjhGbJUGOjI(B. (3jHOC GdcJGH HJSdjW GdVhA Ydi GdBaGb GdYdejI dLZQGajG GdGbJUGOjI, Ke jfJbd Edi OQGSI GdYdGbI Hjf GdLZQGajG GdGbJUGOjI hGdJfejI GdecGfjI(B. (3HYO Pdc, jJfGhd GdcJGH GdeJZjQGJ GdLjhGbJUGOjI ddfbd GdYGdej hGdYdGbGJ GdGbJUGOjI GdecGfjI dCfXeI Gdfbd hNUGFUg(B. (3ceG jSJYQV GdcJGH GdJLGQI GdOhdjI GdeYGUQI hGdeJZjQGJ GdLjhSjGSjI GdGbJUGOjI, hjfJgj HOQGSI GdGfYcGSGJ GdLZQGajI ddeJZjQGJ GdLjhSjGSjI hGdLjhGbJUGOjI(B. (3jgOa GdcJGH Edi JbOje QDjI eJcGedI Yf cjajI JCKjQ GdYhGed GdLZQGajI hGdLjhSjGSjI hGdLjhGbJUGOjI Ydi GdJaGYdGJ GdGbJUGOjI GdOhdjI(B.s
(3GdedGMb U(B.277 (3GdeQGLY U(B.269s
Keywords: (3GdLZQGajG GdEbJUGOjI (B- (3GdJLGQI GdOhdjIs; (3GdLZQGajG GdSjGSjI(B- (3GdJcfhdhLjGs